Augmentation of unstable pertrochanteric fractures in the osteoporotic elderly patient: operative technique for 1 or 2 head screw systems - Dall'Oca, C.; Maluta, T.; Lavini, F.; Micheloni, G. M.; Bondi, M.; Magnan, B. (Acta Biomedica Atenei Parmensis, 2014)
The incidence of proximal femoral fractures has substantially risen in the elderly. This rise has been attributed to an increase in their life span and the underlying poor bone stock and osteoporosis. One of the main reasons for revision surgery, reported to be as high as 19%, is the cut-out of the fixation device at the apex of the femoral head. Augmentation, facilitated by injecting cement (PMMA) around the apex of the proximal screw of the fixation device is considered a useful method with regards to the increased purchase between the bone and implant interface. The aim of this study is the description of the cement Augmentation operative technique for unstable osteoporotic pertrochanteric fractures with 1-2 femoral head screw devices.